Logic : the essentials of deductive reasoning - Agapay, Ramon B. (Mandaluyong City, Philippines : National Book Store, 1991)
This book is an attempt to make the study of logic easy, interesting and fruitful. Toward this end, topic
1. The study of logic -- 2. The nature of concepts -- 3. Kinds of concepts -- 4. Terms as verbal concepts -- 5. The proposition -- 6. The four categoricals -- 7. Opposition -- 8. Education -- 9. The syllogism -- 10. The rules of syllogism -- 11. Moods and figures -- 12. First and second figures -- 13. The third and fourth figures -- 14. Syllogistic Variations -- 15. The Hypothetical Syllogism -- 16. The Fallacies -- 17. AD Hominem Arguments.
Includes bibliographical references.
Keywords: PHILOSOPHY